ChemInform Abstract: Keeping it Small, Polar, and Non‐Flat: Diversely Functionalized Building Blocks Containing the Privileged 5, 6, 7, 8‐Tetrahydro[1, 2, 4]triazolo[4, 3‐a]‐ and [1, 5‐a]pyridine Cores. Issue 27 (16th June 2016) - Mishchuk, Alexander; Shtil, Natalia; Poberezhnyk, Mykola; Nazarenko, Konstiantyn; Savchenko, Timur; Tolmachev, Andrey; Krasavin, Mikhail
Abstract: Different sets of functionalized building blocks, e.